A Process-Based Differentiated Instruction Model for Short Story Writing to Overcome Students’ Learning Difficulties - Faridah Eriyaningsih; Haryadi Haryadi; Nas Haryati Setyaningsih (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Process-Based Differentiated Short Story Writing Instruction Model (PDSSW) was developed to address students’ learning difficulties in learning to write short stories. The development of the model considered students’ individual characteristics as well as the stages of the writing process. This study aimed to develop and examine the effectiveness of the PDSSW model in improving students’ writing skills. This study employed a Research and Development (R&D) method based on the Borg and Gall model and was conducted at the senior high school level. Data was collected through observations, questionnaires, and assessments using pre-tests and post-tests. The PDSSW model consists of eight instructional syntax stages. The effectiveness of the model was tested using a paired-samples t-test and the N-Gain score. The results showed a significant improvement in students’ writing skills, with the average post-test score increasing from 73,42 to 89,16. These findings indicate that the PDSSW model is an effective instructional model that not only enhances writing skills but also promotes creative thinking. This model contributes to the development of knowledge in the field of writing instruction through the integration of a process-based approach and differentiated learning, while also providing practical benefits for teachers, curriculum developers, and educational stakeholders in improving the quality of literacy instruction. More broadly, this model contributes to the strengthening of literacy culture, the development of students’ creativity, and the enhancement of language competencies that are relevant to societal needs and educational challenges.